Ultrasonic-weldable halogen-free flame-retardant polyamide composite material and preparation method thereof
By using modified PA66 and nylon MXD6, combined with toughening agent and glass fiber, the problem of insufficient welding strength in ultrasonic welding of existing nylon composite materials has been solved, and higher welding strength and product quality have been achieved.
Patent Information
- Application Number
- CN202411988290.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-15
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The welding strength of existing nylon composite materials is insufficient during ultrasonic welding, which can easily lead to the welded part falling off and cracks near the welding interface, affecting product quality.
Modified PA66 and nylon MXD6 are used as main materials, combined with toughening agent, glass fiber and special halogen-free flame retardant, and the mechanical strength and welding strength of the material are improved through the preparation method of modified PA66 and the processing technology of twin screw extruders.
It significantly improves the welding strength of polyamide composite materials, solves the problems of shedding and cracks in the welding parts, and improves the quality and yield of the product.
Smart Images

Figure BDA0005223087570000021 
Figure BDA0005223087570000061 
Figure BDA0005223087570000071
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyamide composite materials, and in particular to an ultrasonically weldable halogen-free flame-retardant polyamide composite material and a preparation method thereof. Background Art
[0002] Ultrasonic welding is a fast, clean and effective assembly process. It is a method used to assemble and process thermoplastic plastic accessories and some composite components. It is used for bonding plastic products, plastic products to metal accessories and other non-plastic materials. Ultrasonic welding is a process in which an ultrasonic generator converts a 50Hz or 60Hz current into high-frequency electrical energy of 15kHz, 20kHz, 30kHz or 40kHz. This high-frequency electrical energy is converted into mechanical motion of the same frequency by a transducer, and then transmitted to the welding head through a set of amplitude modulator devices that can change the amplitude. The welding head transmits the received vibration energy to the interface of the plastic parts to be welded. In this area, the vibration energy is converted into heat energy by friction, melting the plastic. After the vibration stops, the short-term pressure maintained on the plastic parts causes the two plastic parts to solidify into one in a molecular connection.
[0003] Existing adapter housings, mobile phone back covers, cooling fan housings, battery housings and other plastic parts are sealed and fixed, mostly using nylon composite materials for ultrasonic welding. However, the ultrasonic welding performance of conventional nylon composite materials is relatively poor, and the welding strength is insufficient, which can easily lead to problems such as the welding part falling off and cracks appearing near the welding interface, affecting product quality. Summary of the invention
[0004] In order to overcome the shortcomings and deficiencies in the prior art, one of the objectives of the present invention is to provide an ultrasonically weldable halogen-free flame-retardant polyamide composite material.
[0005] The second object of the present invention is to provide a method for preparing an ultrasonically weldable halogen-free flame-retardant polyamide composite material, which has simple operation, convenient control, high production efficiency, low production cost, and can be used for large-scale production.
[0006] One of the purposes of the present invention is achieved by the following technical solution: An ultrasonically weldable halogen-free flame-retardant polyamide composite material comprises the following raw materials in parts by weight:
[0007]
[0008] The ultrasonically weldable halogen-free flame-retardant polyamide composite material uses modified PA66 and nylon MXD6 as main materials, which ensure the basic mechanical strength, toughness and barrier properties of the polyamide composite material and have excellent dimensional stability. The modified PA66 has lower hygroscopicity, more active groups after heating and releases more hydrophobic groups at the same time, which is conducive to ultrasonic welding. Nylon MXD6 is an amorphous material and is easier to ultrasonically weld. First, the atomic arrangement of nylon MXD6 is disordered and does not have the lattice structure of crystalline materials. During the ultrasonic welding process, this disordered structure enables the material to better adapt to the high-frequency vibration during welding, because the lattice structure will have a certain obstruction to the vibration, while the amorphous material has no such obstruction, and the energy can be transmitted more effectively, making the material in the welding area easier to be activated, which promotes welding. Secondly, nylon MXD6 has good elastic deformation ability. When ultrasonic waves exert pressure and vibration, nylon MXD6 can produce appropriate elastic deformation, so that the welding surfaces can fit better and more closely, which is conducive to concentrating ultrasonic energy in the welding area and improving the welding effect. The synergistic effect of the two significantly improves the welding strength, effectively solving the problems of the welding part falling off and cracks appearing near the welding interface after ultrasonic welding of polyamide composite materials; in addition, the addition of toughening agent and glass fiber is conducive to improving the strength of the material. The added special halogen-free flame retardant has a low melting point, which is conducive to ultrasonic welding. Since the flame retardant has good fluidity and better dispersion effect, the flame retardant is more uniformly dispersed, which improves the flame retardant effect. The added special chain extender has a low melting point and can provide more active groups, has excellent adhesion, provides more welding anchor points for ultrasonic welding, and further improves the welding strength. The halogen-free flame retardant polyamide composite material is particularly suitable for ultrasonically welded plastic parts.
[0009] Preferably, the preparation method of each modified PA66 comprises the following steps:
[0010] (R1), take 100 parts of organic solvent, 20-30 parts of PA66, 10-20 parts of N-isopropylacrylamide and 1-5 parts of initiator solution by weight, and set aside;
[0011] (R2), adding PA66 and N-isopropylacrylamide to an organic solvent, heating to 50-60° C., stirring and dissolving to obtain a mixed solution;
[0012] (R3), maintaining the system temperature at 70-100° C. under nitrogen protection, adding the initiator solution dropwise to the mixed solution while stirring for 2-3 hours, and continuing the reaction for 4 hours to obtain a reaction product;
[0013] (R4) cooling, precipitating, filtering, washing and drying the reaction product to obtain modified PA66.
[0014] By adopting the above technical scheme, PA66 and N-isopropylacrylamide are polymerized under nitrogen protection, 70-100°C temperature and the action of initiator to obtain modified PA66. N-isopropylacrylamide is grafted on the basis of PA66, which has stronger temperature sensitivity. After heating, more active groups are produced and more hydrophobic groups are released at the same time, which is beneficial to ultrasonic welding and improves welding strength.
[0015] Preferably, the organic solvent is dimethylformamide and / or dimethyl sulfoxide; the initiator solution is a mixture of an initiator and an organic solvent in a weight ratio of 1-5:100, and the initiator is benzoyl peroxide or azobisisobutyronitrile.
[0016] Preferably, the relative viscosity of the nylon MXD6 is 2.2-2.5; the other additive is a toner. Further, the toner can be selected from organic black YS667.
[0017] Preferably, the toughening agent is at least one of SEBS-g-MAH, SBS-g-MAH or POE-g-MAH.
[0018] Using the above technical solution, more preferably, the toughening agent is a mixture of SEBS-g-MAH and POE-g-MAH in a weight ratio of 5:1. The synergistic effect of SEBS-g-MAH and POE-g-MAH not only significantly improves the impact resistance and processing performance of the material, but also increases its elongation, so that the material can better absorb energy when subjected to external force impact, is not easy to break, and effectively reduces the water absorption rate of the material, which is conducive to ultrasonic welding.
[0019] Preferably, the antioxidant is a combination of antioxidant 1098 and antioxidant S9228.
[0020] By adopting the above technical scheme, further, the antioxidant is a mixture of antioxidant 1098 and antioxidant S9228 in a weight ratio of 2:1. The two work synergistically to improve the antioxidant effect, further improve the thermal stability of the material, reduce thermal oxidation degradation during processing, and thus improve the quality and yield of the product.
[0021] Preferably, the halogen-free flame retardant is aluminum diisobutylphosphinate.
[0022] By adopting the above technical scheme, aluminum diisobutylphosphinate is added as a flame retardant to polymer materials such as nylon, which significantly improves the flame retardant properties of the material. Ultrasonic welding can melt it, which is beneficial to ultrasonic welding and avoids uneven flow affecting the flame retardant effect.
[0023] Preferably, the chain extender is an ethylene-maleic anhydride alternating copolymer having a Vicat softening point of 150° C. and a maleic anhydride group content greater than 78 wt %.
[0024] By adopting the above technical scheme, the ethylene-maleic anhydride alternating copolymer has a low melting point and can provide more maleic anhydride active groups, has excellent adhesion, provides more welding anchor points for ultrasonic welding, and further improves the welding strength.
[0025] Preferably, the glass fiber is a high modulus glass fiber, the monofilament diameter of the glass fiber is 8-12 μm, and the fiber length is 2-3 mm.
[0026] By adopting the above technical solution, the material has higher strength, excellent rigidity and bending resistance, and can maintain a stable shape when subjected to stress. Preferably, the glass fiber is selected from Jushi ECS10-3-568H.
[0027] The second object of the present invention is achieved by the following technical solution: The preparation method of the above-mentioned ultrasonically weldable halogen-free flame-retardant polyamide composite material comprises the following steps:
[0028] (S1) Take modified PA66, nylon MXD6, toughening agent, antioxidant, halogen-free flame retardant, chain extender, glass fiber and other additives according to weight parts and set aside;
[0029] (S2), after uniformly mixing the modified PA66, nylon MXD6, toughening agent, antioxidant, halogen-free flame retardant, chain extender, glass fiber and other additives, extruding and granulating through a twin-screw extruder to obtain an ultrasonically weldable halogen-free flame retardant polyamide composite material;
[0030] Among them, the processing temperatures of each section of the twin-screw extruder starting from the feeding section are: 200℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, the head temperature is 270-290℃, and the screw speed is 400-600r / min.
[0031] The beneficial effects of the present invention are as follows: the ultrasonically weldable halogen-free flame-retardant polyamide composite material of the present invention uses modified PA66 and nylon MXD6 as main materials, which ensures the basic mechanical strength, toughness and barrier properties of the polyamide composite material and has excellent dimensional stability; the modified PA66 has lower hygroscopicity, more active groups after heating and releases more hydrophobic groups at the same time, which is beneficial to ultrasonic welding; nylon MXD6 is an amorphous material and is easier to ultrasonically weld; firstly, the atomic arrangement of nylon MXD6 is disordered and does not have the lattice structure of crystalline materials; during the ultrasonic welding process, this disordered structure enables the material to better adapt to the high-frequency vibration during welding, because the lattice structure will have a certain obstacle to the vibration, while the amorphous material does not have such an obstacle, and the energy can be transmitted more effectively, so that the material in the welding area is more easily activated, which promotes welding; secondly, nylon MXD6 has good elasticity. The nylon MXD6 has good elastic deformation ability. When the ultrasonic wave applies pressure and vibration, the nylon MXD6 can produce appropriate elastic deformation, so that the welding surfaces can fit better and more closely, which is conducive to the concentration of ultrasonic energy in the welding area and the improvement of welding effect. The synergistic effect of the two can significantly improve the welding strength, and effectively solve the problems of the welding part falling off and cracks appearing near the welding interface after ultrasonic welding of the polyamide composite material. In addition, the addition of toughening agent and glass fiber is conducive to improving the strength of the material. The added special halogen-free flame retardant has a low melting point, which is conducive to ultrasonic welding. Due to the good fluidity and better dispersion of the flame retardant, the flame retardant is more uniformly dispersed, which improves the flame retardant effect. The added special chain extender has a low melting point and can provide more active groups, and has excellent adhesion, which provides more welding anchor points for ultrasonic welding and further improves the welding strength. The halogen-free flame retardant polyamide composite material is particularly suitable for plastic parts welded by ultrasonic welding.
[0032] The preparation method of the invention has the advantages of simple operation, convenient control, high production efficiency and low production cost, and can be used for large-scale production. DETAILED DESCRIPTION
[0033] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.
[0034] Example 1
[0035] An ultrasonically weldable halogen-free flame-retardant polyamide composite material comprises the following raw materials in parts by weight:
[0036]
[0037] The preparation method of each modified PA66 comprises the following steps:
[0038] (R1), take 100 parts of organic solvent, 25 parts of PA66, 15 parts of N-isopropylacrylamide and 3 parts of initiator solution by weight, and set aside;
[0039] (R2), adding PA66 and N-isopropylacrylamide to an organic solvent, heating to 55° C. and stirring to dissolve, to obtain a mixed solution;
[0040] (R3), maintaining the system temperature at 85° C. under nitrogen protection, adding the initiator solution dropwise to the mixed solution while stirring for 2.5 hours, and continuing the reaction for 4 hours to obtain a reaction product;
[0041] (R4) cooling, precipitating, filtering, washing and drying the reaction product to obtain modified PA66.
[0042] The organic solvent is dimethylformamide; the initiator solution is prepared by mixing an initiator and dimethylformamide in a weight ratio of 3:100, and the initiator is azobisisobutyronitrile.
[0043] The relative viscosity of the nylon MXD6 is 2.2; the other auxiliary agent is the color powder organic black YS667.
[0044] The toughening agent is a mixture of SEBS-g-MAH and POE-g-MAH in a weight ratio of 5:1.
[0045] The antioxidant is a mixture of antioxidant 1098 and antioxidant S9228 in a weight ratio of 2:1.
[0046] The halogen-free flame retardant is aluminum diisobutylphosphinate.
[0047] The chain extender is an ethylene-maleic anhydride alternating copolymer with a Vicat softening point of 150° C., wherein the maleic anhydride group content is greater than 78% by weight, and the molar ratio of ethylene to maleic anhydride is 1:1.
[0048] The glass fiber is selected from Jushi ECS10-3-568H.
[0049] The method for preparing the ultrasonically weldable halogen-free flame-retardant polyamide composite material comprises the following steps:
[0050] (S1) Take modified PA66, nylon MXD6, toughening agent, antioxidant, halogen-free flame retardant, chain extender, glass fiber and other additives according to weight parts and set aside;
[0051] (S2), after uniformly mixing the modified PA66, nylon MXD6, toughening agent, antioxidant, halogen-free flame retardant, chain extender, glass fiber and other additives, extruding and granulating through a twin-screw extruder to obtain an ultrasonically weldable halogen-free flame retardant polyamide composite material;
[0052] Among them, the processing temperatures of each section of the twin-screw extruder starting from the feeding section are: 200℃, 270℃, 270℃, 270℃, 280℃, 280℃, 280℃, 270℃, 270℃, 270℃, 270℃, the head temperature is 280℃, and the screw speed is 500r / min.
[0053] Example 2
[0054] An ultrasonically weldable halogen-free flame-retardant polyamide composite material comprises the following raw materials in parts by weight:
[0055]
[0056] The preparation method of each modified PA66 comprises the following steps:
[0057] (R1), take 100 parts of organic solvent, 20 parts of PA66, 10 parts of N-isopropylacrylamide and 1 part of initiator solution by weight, and set aside;
[0058] (R2), adding PA66 and N-isopropylacrylamide to an organic solvent, heating to 50° C. and stirring to dissolve, to obtain a mixed solution;
[0059] (R3), maintaining the system temperature at 70° C. under nitrogen protection, adding the initiator solution dropwise to the mixed solution while stirring for 2 h, and continuing the reaction for 4 h to obtain a reaction product;
[0060] (R4) cooling, precipitating, filtering, washing and drying the reaction product to obtain modified PA66.
[0061] The organic solvent is dimethylformamide; the initiator solution is prepared by mixing an initiator and dimethylformamide at a weight ratio of 1:100, and the initiator is azobisisobutyronitrile.
[0062] The relative viscosity of the nylon MXD6 is 2.2; the other auxiliary agent is the color powder organic black YS667.
[0063] The toughening agent is a mixture of SEBS-g-MAH and POE-g-MAH in a weight ratio of 5:1.
[0064] The antioxidant is a mixture of antioxidant 1098 and antioxidant S9228 in a weight ratio of 2:1.
[0065] The halogen-free flame retardant is aluminum diisobutylphosphinate.
[0066] The chain extender is an ethylene-maleic anhydride alternating copolymer with a Vicat softening point of 150° C., wherein the maleic anhydride group content is greater than 78% by weight, and the molar ratio of ethylene to maleic anhydride is 1:1.
[0067] The glass fiber is selected from Jushi ECS10-3-568H.
[0068] The method for preparing the ultrasonically weldable halogen-free flame-retardant polyamide composite material comprises the following steps:
[0069] (S1) Take modified PA66, nylon MXD6, toughening agent, antioxidant, halogen-free flame retardant, chain extender, glass fiber and other additives according to weight parts and set aside;
[0070] (S2), after uniformly mixing the modified PA66, nylon MXD6, toughening agent, antioxidant, halogen-free flame retardant, chain extender, glass fiber and other additives, extruding and granulating through a twin-screw extruder to obtain an ultrasonically weldable halogen-free flame retardant polyamide composite material;
[0071] Among them, the processing temperatures of each section of the twin-screw extruder starting from the feeding section are: 200℃, 270℃, 270℃, 270℃, 280℃, 280℃, 280℃, 270℃, 270℃, 270℃, 270℃, the head temperature is 280℃, and the screw speed is 500r / min.
[0072] Example 3
[0073] An ultrasonically weldable halogen-free flame-retardant polyamide composite material comprises the following raw materials in parts by weight:
[0074]
[0075] The preparation method of each modified PA66 comprises the following steps:
[0076] (R1), take 100 parts of organic solvent, 30 parts of PA66, 20 parts of N-isopropylacrylamide and 5 parts of initiator solution by weight, and set aside;
[0077] (R2), adding PA66 and N-isopropylacrylamide to an organic solvent, heating to 60° C. and stirring to dissolve, to obtain a mixed solution;
[0078] (R3), maintaining the system temperature at 100° C. under nitrogen protection, adding the initiator solution dropwise to the mixed solution while stirring for 3 hours, and continuing the reaction for 4 hours to obtain a reaction product;
[0079] (R4) cooling, precipitating, filtering, washing and drying the reaction product to obtain modified PA66.
[0080] The organic solvent is dimethylformamide; the initiator solution is prepared by mixing an initiator and dimethylformamide in a weight ratio of 5:100, and the initiator is azobisisobutyronitrile.
[0081] The relative viscosity of the nylon MXD6 is 2.2; the other auxiliary agent is the color powder organic black YS667.
[0082] The toughening agent is a mixture of SEBS-g-MAH and POE-g-MAH in a weight ratio of 5:1.
[0083] The antioxidant is a mixture of antioxidant 1098 and antioxidant S9228 in a weight ratio of 2:1.
[0084] The halogen-free flame retardant is aluminum diisobutylphosphinate.
[0085] The chain extender is an ethylene-maleic anhydride alternating copolymer with a Vicat softening point of 150° C., wherein the maleic anhydride group content is greater than 78% by weight, and the molar ratio of ethylene to maleic anhydride is 1:1.
[0086] The glass fiber is selected from Jushi ECS10-3-568H.
[0087] The method for preparing the ultrasonically weldable halogen-free flame-retardant polyamide composite material comprises the following steps:
[0088] (S1) Take modified PA66, nylon MXD6, toughening agent, antioxidant, halogen-free flame retardant, chain extender, glass fiber and other additives according to weight parts and set aside;
[0089] (S2), after uniformly mixing the modified PA66, nylon MXD6, toughening agent, antioxidant, halogen-free flame retardant, chain extender, glass fiber and other additives, extruding and granulating through a twin-screw extruder to obtain an ultrasonically weldable halogen-free flame retardant polyamide composite material;
[0090] Among them, the processing temperatures of each section of the twin-screw extruder starting from the feeding section are: 200℃, 270℃, 270℃, 270℃, 280℃, 280℃, 280℃, 270℃, 270℃, 270℃, 270℃, the head temperature is 280℃, and the screw speed is 500r / min.
[0091] Example 4
[0092] An ultrasonically weldable halogen-free flame-retardant polyamide composite material comprises the following raw materials in parts by weight:
[0093]
[0094] The preparation method of each modified PA66 comprises the following steps:
[0095] (R1), take 100 parts of organic solvent, 22 parts of PA66, 18 parts of N-isopropylacrylamide and 4 parts of initiator solution by weight, and set aside;
[0096] (R2), adding PA66 and N-isopropylacrylamide to an organic solvent, heating to 55° C. and stirring to dissolve, to obtain a mixed solution;
[0097] (R3), maintaining the system temperature at 90° C. under nitrogen protection, adding the initiator solution dropwise to the mixed solution while stirring for 2 hours, and continuing the reaction for 4 hours to obtain a reaction product;
[0098] (R4) cooling, precipitating, filtering, washing and drying the reaction product to obtain modified PA66.
[0099] The organic solvent is dimethylformamide; the initiator solution is prepared by mixing an initiator and dimethylformamide in a weight ratio of 4:100, and the initiator is azobisisobutyronitrile.
[0100] The relative viscosity of the nylon MXD6 is 2.2; the other auxiliary agent is the color powder organic black YS667.
[0101] The toughening agent is a mixture of SEBS-g-MAH and POE-g-MAH in a weight ratio of 5:1.
[0102] The antioxidant is a mixture of antioxidant 1098 and antioxidant S9228 in a weight ratio of 2:1.
[0103] The halogen-free flame retardant is aluminum diisobutylphosphinate.
[0104] The chain extender is an ethylene-maleic anhydride alternating copolymer with a Vicat softening point of 150° C., wherein the maleic anhydride group content is greater than 78% by weight, and the molar ratio of ethylene to maleic anhydride is 1:1.
[0105] The glass fiber is selected from Jushi ECS10-3-568H.
[0106] The method for preparing the ultrasonically weldable halogen-free flame-retardant polyamide composite material comprises the following steps:
[0107] (S1) Take modified PA66, nylon MXD6, toughening agent, antioxidant, halogen-free flame retardant, chain extender, glass fiber and other additives according to weight parts and set aside;
[0108] (S2), after uniformly mixing the modified PA66, nylon MXD6, toughening agent, antioxidant, halogen-free flame retardant, chain extender, glass fiber and other additives, extruding and granulating through a twin-screw extruder to obtain an ultrasonically weldable halogen-free flame retardant polyamide composite material;
[0109] Among them, the processing temperatures of each section of the twin-screw extruder starting from the feeding section are: 200℃, 270℃, 270℃, 270℃, 280℃, 280℃, 280℃, 270℃, 270℃, 270℃, 270℃, the head temperature is 280℃, and the screw speed is 500r / min.
[0110] Comparative Example 1
[0111] The difference between this comparative example and Example 1 is:
[0112] The modified PA66 is replaced by PA66.
[0113] Comparative Example 2
[0114] The difference between this comparative example and Example 1 is:
[0115] The nylon MXD6 is replaced by PA6.
[0116] Comparative Example 3
[0117] The difference between this comparative example and Example 1 is:
[0118] The toughening agent is a mixture of SBS-g-MAH and EPDM-g-MAH in a weight ratio of 5:1.
[0119] Performance Testing
[0120] The polyamide composite materials of Examples 1-4 and Comparative Examples 1-3 were tested for tensile strength, flexural strength, notched impact strength, flame retardancy, and ultrasonic welding strength. The testing methods are as follows:
[0121] Tensile strength: tested according to ISO 527 Determination of tensile properties of plastics, the test condition is 20mm / min;
[0122] Bending strength: tested according to ISO 178 Plastics. Determination of bending properties, the test condition is 40mm / min;
[0123] Notched impact strength: tested according to ISO 180 Plastics - Determination of cantilever beam impact strength of hard materials, the test condition is 23℃;
[0124] Flame retardancy: According to UL94 flame retardancy test, sample thickness 0.8mm;
[0125] Ultrasonic welding strength: Two identical samples are ultrasonically welded, with an ultrasonic welding pulse time of 2s, a welding pressure of 0.2-0.4Mpa, and a cooling time of 30s to obtain a sample; the welded sample is prepared into a standard tensile specimen, and an axial tensile force is applied to the tensile specimen by a tensile testing machine until the tensile specimen breaks, and the maximum tensile force at the time of fracture is recorded, and the tensile strength of the welded joint is calculated based on the cross-sectional area of the tensile specimen. The maximum tensile force is recorded as F Newton, the cross-sectional area of the tensile specimen is A square meters, and the tensile strength σ = F / A (in Pa), which is the ultrasonic welding strength.
[0126] The test results are shown in Table 1 below:
[0127]
[0128] As can be seen from Table 1 above, the ultrasonically weldable halogen-free flame-retardant polyamide composite material uses modified PA66 and nylon MXD6 as main materials, which ensures the basic mechanical strength and toughness of the polyamide composite material and significantly improves the welding strength. The halogen-free flame-retardant polyamide composite material is particularly suitable for ultrasonically welded plastic parts.
[0129] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. An ultrasonically weldable halogen-free flame-retardant polyamide composite material, characterized in that: The invention comprises the following raw materials in parts by weight:
2. The ultrasonically weldable halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The preparation method of each modified PA66 comprises the following steps: (R1), take 100 parts of organic solvent, 20-30 parts of PA66, 10-20 parts of N-isopropylacrylamide and 1-5 parts of initiator solution by weight, and set aside; (R2), adding PA66 and N-isopropylacrylamide to an organic solvent, heating to 50-60° C., stirring and dissolving to obtain a mixed solution; (R3), maintaining the system temperature at 70-100° C. under nitrogen protection, adding the initiator solution dropwise to the mixed solution while stirring for 2-3 hours, and continuing the reaction for 4 hours to obtain a reaction product; (R4) cooling, precipitating, filtering, washing and drying the reaction product to obtain modified PA66.
3. The ultrasonically weldable halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The organic solvent is dimethylformamide and / or dimethyl sulfoxide; the initiator solution is prepared by mixing the initiator and the organic solvent in a weight ratio of 1-5:100, and the initiator is benzoyl peroxide or azobisisobutyronitrile.
4. The ultrasonically weldable halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The relative viscosity of the nylon MXD6 is 2.2-2.5; and the other auxiliary agent is toner.
5. The ultrasonically weldable halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The toughening agent is at least one of SEBS-g-MAH, SBS-g-MAH or POE-g-MAH.
6. The ultrasonically weldable halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The antioxidant is a combination of antioxidant 1098 and antioxidant S9228.
7. The ultrasonically weldable halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The halogen-free flame retardant is aluminum diisobutylphosphinate.
8. The ultrasonically weldable halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The chain extender is an ethylene maleic anhydride alternating copolymer with a Vicat softening point of 150° C., wherein the maleic anhydride group content is greater than 78 wt %.
9. The ultrasonically weldable halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: The glass fiber is a high modulus glass fiber, and the monofilament diameter of the glass fiber is 8-12 μm and the fiber length is 2-3 mm.
10. A method for preparing an ultrasonically weldable halogen-free flame-retardant polyamide composite material according to any one of claims 1 to 9, characterized in that: The steps include: (S1) Take modified PA66, nylon MXD6, toughening agent, antioxidant, halogen-free flame retardant, chain extender, glass fiber and other additives according to weight parts and set aside; (S2), after uniformly mixing the modified PA66, nylon MXD6, toughening agent, antioxidant, halogen-free flame retardant, chain extender, glass fiber and other additives, extruding and granulating through a twin-screw extruder to obtain an ultrasonically weldable halogen-free flame retardant polyamide composite material; Among them, the processing temperatures of each section of the twin-screw extruder starting from the feeding section are: 200℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, 260-280℃, the head temperature is 270-290℃, and the screw speed is 400-600r / min.
Citation Information
Cited By
Ultrasonic-assisted welding method for all tabs of cylindrical battery
CN121245200A